2010
DOI: 10.1001/archneurol.2009.296
|View full text |Cite
|
Sign up to set email alerts
|

Scoliosis Surgery in Children With Neuromuscular Disease

Abstract: Background: Scoliosis is a frequent complication of pediatric neuromuscular disease (NMD). Scoliosis surgery in children with NMD is thought to carry greater morbidity and mortality. Objectives: To study demographics, comorbidities, outcomes, and hospitalization expenditures among children with NMD undergoing scoliosis surgery. Design: Using the Kids Inpatient Database, a large allpayer US database of hospital discharges among children and adults younger than 20 years, we studied children undergoing scoliosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 37 publications
2
32
1
Order By: Relevance
“…Pulmonary complications are a prominent cause of morbidity and mortality in these high-risk patients [8,32], with complication rates as high as 39 % [14]. In the current review, the overall PR is 22.71 % with 97.8 % variability.…”
Section: Pulmonary Complicationsmentioning
confidence: 84%
See 1 more Smart Citation
“…Pulmonary complications are a prominent cause of morbidity and mortality in these high-risk patients [8,32], with complication rates as high as 39 % [14]. In the current review, the overall PR is 22.71 % with 97.8 % variability.…”
Section: Pulmonary Complicationsmentioning
confidence: 84%
“…Recently, large database studies on complications of scoliosis surgery have been published [7,9,13,14]. Although these studies benefit from large patient populations, they might be prone to underreporting.…”
Section: Introductionmentioning
confidence: 99%
“…Patient BMI is calculated by height and weight and categorized according to CDC BMI-for-age charts [8]. Per CDC guidelines, pediatric patients with less than the fifth percentile BMIfor-age are categorized as underweight; patients with BMIfor-age greater than the eighty-fifth percentile are categorized as overweight; and patients with BMI-for-age greater than the ninety-fifth percentile are categorized as obese (Appendix 2) [3,4,14]. Of the comorbidities collected by the ACS NSQIP 1 , only a history of asthma occurred with sufficient frequency to be used for our analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Although no cases of mortality are reported in most prior series, 4,[17][18][19][23][24][25] Barsdorf et al reported a mortality rate of 1.6% (7 of 437 cases) following surgery for neuromuscular scoliosis, based on the National Inpatient Sample between 1997 and 2003. 2 In an effort to assess for potential differences in the rates of new neurological deficit associated with type of instrumentation used, we assessed these rates in cases that used only a single type of instrumentation, specifically pedicle screws, anterior screws, hooks, or wires. Pedicle screw-only and hook-only constructs had comparable overall rates of new neurological deficits.…”
Section: Lessons Learnedmentioning
confidence: 99%